The strange political character of Confesión a Laura. An analysis from the concept of Esthetic Regime by Jacques Rancière (2017)
Confesión a Laura turns the Bogotazo into another time and another space, different from those accustomed to reworking with the greatest of scientistic minds those historians sympathetic to the impracticable objectivity and the panoramic format, which often fog certain key details of memory. And it is in this sense how the film dialogues in its stage and plot development with the concept of aesthetic regime of Rancière, proposing a regime of historicity that conceives of fiction, on the contrary, as the only perceptual procedure to think reality in any of Its possibilities. This dialogue is presented in this article under a methodology of qualitative analysis, comparing the scenic aspects of the film with the conceptualization of aesthetic regime offered by the philosopher Rancière.